Mild ventriculomegaly from fetal consultation to neurodevelopmental assessment: A single center experience and review of the literature. (November 2018) - Scelsa, Barbara; Rustico, Mariangela; Righini, Andrea; Parazzini, Cecilia; Balestriero, Marina Antonella; Introvini, Paola; Spaccini, Luigina; Mastrangelo, Massimo; Lista, Gianluca; Zuccotti, Gian Vincenzo; Veggiotti, Pierangelo
Abstract: Objective: The aim of our study was to determine the outcome of fetuses with isolated mild ventriculomegaly, with prenatal imaging work-up, prenatal consultation, delivery and clinical follow-up performed in a single tertiary referring center. Methods: Fetuses with isolated and non-progressive mild ventriculomegaly (10–15 mm) were included in the study. Inclusion criteria were as follows: singleton pregnancies, normal chromosomal analysis, normal serological evaluation of TORCH, fetal ultrasound and MRI excluding additional CNS or extra-CNS malformations. The prenatal consultation consisted in discussing the prognosis of ventriculomegaly, according to the literature. The postnatal follow-up protocol included a neuroradiological investigation (cranial ultrasound or MRI), neurological and pediatric examinations. The Griffiths Scales were used to assess the neurodevelopmental outcome. Results: Thirty newborns were included in follow-up. The postnatal neuroradiological investigations confirmed the ventriculomegaly as an isolated finding in all cases except one. Nineteen children were available for formal neurodevelopmental testing. In our case series, 93.3% of the children had a favorable outcome or mild anomalies. Two children (6.6%) with mild ventriculomegaly were diagnosed as having rare genetic conditions. The Griffiths developmental quotients were normal (mean General Quotient 98.3) at the latest assessment (mean age 20.8 months) in all but one case. Discussion: Most children in our case series had a favorable outcome, as described in the literature. Even though a large quantity of data is now available on ventriculomegaly, fetal consultation remains challenging and requires caution. The diagnostic work-up of pregnancies diagnosed with mild ventriculomegaly must be very meticulous and include TORCH evaluation, microarray, serial ultrasounds to exclude progression, and a fetal MRI. However, despite accurate screening, there are more complex conditions in which ventriculomegaly can be the only non-specific finding in fetal life, making postnatal follow up mandatory. Highlights: Prenatal work-up in VM should include TORCH evaluation, microarray, serial ultrasounds to exclude progression, and a fetal MRI. In VM a post-natal follow-up is mandatory to exclude rare conditions. Long term follow-up should include a formal neurodevelopmental test. Brain volumetric and ADC studies seem promising in helping to understand the impact of mild VM on neurodevelopmental outcome.